Addressing the design-implementation gap of sustainable business models by prototyping: A tool for planning and executing small-scale pilots. (10th May 2020) - Baldassarre, Brian; Konietzko, Jan; Brown, Phil; Calabretta, Giulia; Bocken, Nancy; Karpen, Ingo O.; Hultink, Erik Jan
Abstract: Next to the redesign of industrial products and processes, sustainable business model innovation is a strategic approach to integrate environmental and social concerns into the objectives and operations of organizations. One of the major challenges of this approach is that many promising business model ideas fail to reach the market, which is needed to achieve impact. In the literature, the issue is referred to as a "design-implementation gap." This paper explores how that critical gap may be bridged. In doing so, we contribute to sustainable business model innovation theory and practice. We contribute to theory by connecting sustainable business model innovation with business experimentation and strategic design, two innovation approaches that leverage prototyping as a way to iteratively implement business ideas early on. Using a design science research methodology, we combine theoretical insights from these three literatures into a tool for setting up small-scale pilots of sustainable business models . We apply, evaluate, and improve our tool through a rigorous process by working with nine startups and one multinational company. As a result, we provide normative theory in terms of the sustainable business model innovation process, explaining that piloting a prototype forces organizations to simultaneously consider the desirability (i.e., what users want), feasibility (i.e., what is technically achievable), viability (i.e., what is financially possible), and sustainability (i.e., what is economically, socially and environmentally acceptable) of a new business model. Doing so early on is functional to bridge the design-implementation gap of sustainable business models . We contribute to practice with the tool itself, which organizations can use to translate sustainable business model ideas defined "on paper" into small-scale pilots as a first implementation step. We encourage future research building on the limitations of this exploratory study by working with a larger sample of companies through longitudinal case studies, to further explain how these pilots can be executed successfully. Graphical abstract: Image 1 Highlights: Many business model ideas aimed at integrating sustainability into the objectives and operations of organizations fail to reach the market. Prototyping allows bridging this design-implementation gap of sustainable business models by shifting the focus from ideation to execution. We propose a tool that organizations can use to plan and execute small-scale pilots for implementing sustainable business models.